CLASSROOM INTERACTION WITH DIFFERENT SUBJECT BASED ON SINCLAIR AND COULTHARD MODEL - Indahwaty Suwandy; Siti Aisah Ginting; Rita Suswati (Universitas Negeri Medan, 2018)
This study is analysis of classroom interaction between English and Mathematics subject which conducted by teachers and students through communication in classroom interaction. The aims of this study were: (a) To identify the kinds of Initiation-Response-Feedback (IRF) pattern are used by the teacher and students in classroom interaction based on Sinclair and Coulthard Model (1975), and (b) To find out why the Initiation-Response-Feedback (IRF) pattern is dominant in classroom interaction through different subject. The design of the research used qualitative research. To answer the problem of study, the data collected through the following instrument: observation, recording and interviewing which were analyzed by using Sinclair and Coulthard model and a concept of teaching. The results of this research were the following, (a) it was found that in English and Mathematics classroom discourse, as the IR (Initiation-Response) was used more often by teachers and I (Initiation) was used by students in English classroom then IF (Initiation-Feedback) was used by students in Mathematics classroom, (b) the reason why the IRF pattern dominantly appeared based on teacher’s performance which dominantly initiated questions and information was affected by the presage category and context category then the students’ performance which dominantly responded the teachers’ questions and information was affected by the students’ thought processes category.Key words: Classroom interaction, classroom discourse, Sinclair and Coulthard Model, IRF Pattern.